Justice denied : sentencing youth to life in prison - Milliken-Boyd, Kathi; Windell, James O. (New York, NY : Routledge, 2022)
"This book analyzes the impact of the U.S. Supreme Court rulings deeming juvenile life without parole (LWOP) sentences to be cruel and unusual punishment. These Court decisions brought about controversy and resistance in the criminal justice field, while at the same time providing hope for those 2,300 people who never thought they had a chance to experience life as an adult outside prison. By looking in depth at the lives of some of the individuals serving life terms, and understanding both the prosecutors who oppose review and resentencing of juvenile lifers and those who are sincerely following the Supreme Court's guidelines, this book provides a comprehensive understanding of the issues - as well as the people - involved in the sentencing (and potential resentencing) of juveniles to life without the possibility of parole. The authors provide unique, perceptive, and straightforward profiles on some of the prisoners who were ultimately sentenced to LWOP after being involved in criminal offenses committed before their eighteenth birthdays. The book poignantly features the experiences of young people who did not commit a murder yet were still sentenced to life terms, but also delves into the perspectives of the families of victims of juvenile offenders, prosecutors on both sides of the issue, psychologists who have interviewed many of the juvenile lifers, and advocates for change in the way juveniles are treated by the criminal justice system. The decisions in Miller v. Alabama and Montgomery v. Louisiana clearly demonstrated that the Court's view of juveniles evolved over decades to reflect advances in our understanding of the unique characteristics of youth and their involvement in juvenile crimes. This book takes the position that the sentence of life without the possibility of parole for youth is wasteful of both human lives and scarce public resources. The authors write about the human concerns on both sides of the question, and, ultimately, allow readers to make their own decisions about how society should best handle juvenile offenders. This engaging ethnographic treatment will appeal to students and scholars of criminology, corrections, juvenile justice, and delinquency; practitioners working in social policy; and all those interested in a criminal justice system capable of positive outcomes for involved youth"--
Part I. Children getting life -- Condemning children to die in prison -- Part II. Kathi's story about Kevin Boyd -- Is adult prison the only answer? -- How did we get here? -- Kevin Boyd goes to trial -- Part III. Which juveniles receive life sentences? -- Assessing juvenile lifers -- Who gets sentenced to life without parole? -- The supreme court gets involved -- Part IV. The voices of the victims -- Justice for victims -- Victims and restorative justice -- Part V. The prosecuting attorneys -- Resistance to understanding and compassion -- Miller and the prosecutors -- Part VI. Juveniles in prison -- The rarest of the rare: who deserves life without parole? -- What happens to juveniles in adult prisons? -- Part VII. Why do we treat vulnerable youth so harshly? -- Why do we treat kids so badly? -- Part VIII. Justice reform -- Where do we go from here?
OCLC-licensed vendor bibliographic record.
Keywords: Life imprisonment -- Moral and ethical aspects -- United States; Juvenile detention -- Moral and ethical aspects -- United States; Juvenile detention -- United States -- Psychological aspects; Juvenile delinquents -- United States -- Psychology; LAW / Criminal Law / Juvenile Offenders; SOCIAL SCIENCE / Criminology